The roles of personality and resilience in associations between combat experiences and posttraumatic stress disorder among Canadian Armed Forces Veterans. (May 2023) - Plouffe, Rachel A.; Nazarov, Anthony; Forchuk, Callista A.; Gervasio, Julia; Le, Tri; Liu, Jenny J.W.; Nouri, Maede S.; Trahair, Cassidy; Walker, Deanna L.; Richardson, J. Don
Abstract: Canadian Armed Forces (CAF) Veterans encounter unique challenges associated with their service. Exposure to service-related traumatic events places them at risk for developing adverse mental health outcomes, including posttraumatic stress disorder (PTSD). Our research aimed to assess whether the HEXACO personality model and resilience impacted associations between combat experiences and PTSD symptomatology in CAF Veterans in the past month. We recruited a sample of 245 CAF Veterans (81 % men; M age  = 48.47, SD age  = 10.34) to complete a battery of questionnaires. PTSD symptoms were significantly associated with more combat experience, lower resilience, lower extraversion, higher emotionality, and lower agreeableness. However, personality traits did not moderate the relationship between combat experiences and PTSD symptoms. Overall, this research can be used to enhance researchers' and clinicians' understanding of personality traits as risk and protective factors for PTSD symptoms.